Psychometric Properties of the Recovery Experiences Questionnaire in Peruvian Teachers of Regular Basic Education - Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Zúñiga, Dámaris Quinteros; Turpo Chaparro, Josué Edison; Romero, Abel Apaza; Murillo, Walter (Frontiers in Education, 2022)
The objective of this study was to analyze the psychometric properties of the Recovery Experiences questionnaire in Peruvian teachers of regular basic education. Instrumental design research, with the participation of 740 regular basic education teachers (494 women and 246 men), whose ages were between 21 and 65 years old (M = 40.22, SD = 9.99). Validity evidence based on internal structure was analyzed using confirmatory factor analysis, based on relation to other variables through correlation analysis, and reliability was calculated using Cronbach's alpha coefficient. The factorial structure of the questionnaire was confirmed (χ2 = 209.683, df = 48, p = 0.000; CFI = 0.986; TLI = 0.981; RMSEA = 0.068; SRMR = .032; WRMR = 0.951); Therefore, the model of 12 items distributed in 4 factors (Distancing, Relaxation, Seeking challenges and Control) is satisfactory and the reliability is acceptable, with α values between .80 and .83. The recovery experiences questionnaire demonstrates validity and reliability for Peruvian regular basic education teachers.